On harmonic functions satisfying nonlocal boundary conditions - Eydelman, S. D.; Firdman, A. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study functions that are harmonic on a strip and satisfy nonlocal boundary conditions, establish constraints that should be imposed on the coefficients in the boundary conditions to guarantee the uniqueness of nonnegative solutions, and present examples when the uniqueness theorems are not true.